Antibiotic use at the ear, nose, and throat outpatient clinic in Bangli Regional Hospital, Bali - Sudiadewi, Ni Putu Eka; Permatananda, Pande Ayu Naya Kasih; Udiyani, Desak Putu Citra; Cahyawati, Putu Nita; Aryastuti, Sri Agung (Indonesian Journal of Pharmacology and Therapy, 2025)
Ear, nose, and throat (ENT) diseases are defined as diseases that occur around the ear, nose, and throat organs, which do not recognize seasons and can affect various ages. The prevalence of ENT diseases in Indonesia is quite high, with the most common therapy being antibiotics. Irrational antibiotics use can lead to increased treatment costs, risk of side effects, and toxicity. This study aimed to evaluate the use of antibiotics among ENT outpatient. This was a cross-sectional study using medical records data from the ENT Outpatient Clinic in Bangli Regional Hospital in 2022 that meet the inclusion criteria. Data were analyzed descriptively and presented in tables or diagrams. A total of 80 samples were evaluated, predominantly aged 18-44 yo (60%), female (53.8%), and diagnosed with chronic suppurative otitis media (20%). The pattern of antibiotic prescription consisted of monotherapy antibiotics (62.5%) in solid dosage forms (58.8%), administered orally (60%), and with a duration of administration ≥ 5 d (82.5%). Patients aged 18-44 yr, both male and female, receiving either monotherapy orpolytherapy antibiotics were predominantly cases of infection (>90%). The results of this study are expected to serve as one of the sources of information for the development of practical clinical guidelines for ENT patients receiving antibiotic therapy, particularly at the Bangli Regional Hospital, Bali.